Co-substitutions of iron and manganese in zirconia. Synthesis, structural, magnetic, mechanical and in vitro evaluation. Issue 1 (January 2020) - Raveendran, Subina; Khan, Mohd Imran K.; Dhayalan, Arunkumar; Kannan, S.
Abstract: Co-substitution of iron and manganese in ZrO2 and the subsequent structural analysis, mechanical, magnetic and in vitro evaluation is presented. Five different compositions have been synthesized by varying the concentrations of iron and manganese addition in ZrO2 system. Characterization results revealed the concomitant effect of dopant concentration and annealing temperature in influencing the phase behaviour of ZrO2 alongside the formation of secondary phase comprising bixbyite [(Fe, Mn)2 O3 ] structure. XPS analysis confirmed the oxidation state of constituent elements in the composite system. Iron and manganese inclusions in ZrO2 facilitated ferrimagnetic characteristics and moreover enhanced magnetization is noticed during the crystallization of (Fe, Mn)2 O3 . Pore free microstructures together with the enhanced hardness and Young's modulus values have been determined in the investigated compositions. In vitro studies displayed good biocompatibility, cell viability and negligible toxicity of ZrO2 system comprising iron and manganese.